Mechanosensitive transcriptional coactivators MRTF‐A and YAP/TAZ regulate nucleus pulposus cell phenotype through cell shape. Issue 12 (22nd October 2019) - Fearing, Bailey V.; Jing, Liufang; Barcellona, Marcos N.; Witte, Savannah Est; Buchowski, Jacob M.; Zebala, Lukas P.; Kelly, Michael P.; Luhmann, Scott; Gupta, Munish C.; Pathak, Amit; Setton, Lori A.
Abstract : Cells of the adult nucleus pulposus (NP) are critically important in maintaining overall disc health and function. NP cells reside in a soft, gelatinous matrix that dehydrates and becomes increasingly fibrotic with age. Such changes result in physical cues of matrix stiffness that may be potent regulators of NP cell phenotype and may contribute to a transition toward a senescent and fibroblastic NP cell with a limited capacity for repair. Here, we investigate the mechanosignaling cues generated from changes in matrix stiffness in directing NP cell phenotype and identify mechanisms that can potentially preserve a biosynthetically active, juvenile NP cell phenotype. Using a laminin‐functionalized polyethylene glycol hydrogel, we show that when NP cells form rounded, multicell clusters, they are able to maintain cytosolic localization of myocardin‐related transcription factor (MRTF)‐A, a coactivator of serum‐response factor (SRF), known to promote fibroblast‐like behaviors in many cells. Upon preservation of a rounded shape, human NP cells similarly showed cytosolic retention of transcriptional coactivator Yes‐associated protein (YAP) and its paralogue PDZ‐binding motif (TAZ) with associated decline in activation of its transcription factor TEA domain family member‐binding domain (TEAD). When changes in cell shape occur, leading to a more spread, fibrotic morphology associated with stronger F‐actin alignment, SRF and TEAD are up‐regulated. However, targeted deletion of either cofactor was not sufficient to overcome shape‐mediated changes observed in transcriptional activation of SRF or TEAD. Findings show that substrate stiffness‐induced promotion of F‐actin alignment occurs concomitantly with a flattened, spread morphology, decreased NP marker expression, and reduced biosynthetic activity. This work indicates cell shape is a stronger indicator of SRF and TEAD mechanosignaling pathways than coactivators MRTF‐A and YAP/TAZ, respectively, and may play a role in the degeneration‐associated loss of NP cellularity and phenotype.—Fearing, B. V., Jing, L., Barcellona, M. N., Witte, S. E., Buchowski, J. M., Zebala, L. P., Kelly, M. P., Luhmann, S., Gupta, M. C., Pathak, A., Setton, L. A. Mechanosensitive transcriptional coactivators MRTF‐A and YAP/TAZ regulate nucleus pulposus cell phenotype through cell shape. FASEB J. 33, 14022‐14035 (2019). www.fasebj.org